2022
DOI: 10.3389/fnut.2022.809865
|View full text |Cite
|
Sign up to set email alerts
|

Quality More Than Quantity: The Use of Carbohydrates in High-Fat Diets to Tackle Obesity in Growing Rats

Abstract: Childhood obesity prevention is important to avoid obesity and its comorbidities into adulthood. Although the energy density of food has been considered a main obesogenic factor, a focus on food quality rather that the quantity of the different macronutrients is needed. Therefore, this study investigates the effects of changing the quality of carbohydrates from rapidly to slowly digestible carbohydrates on metabolic abnormalities and its impact on obesity in growing rats fed a high-fat diet (HFD). Growing rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…At the genus level, treatment of ISR after 4 weeks revealed a higher proportion of Alistipes compared to the NOB group, which might be a bacterial genus of particular interest in the field of obesity since Alistipes is a potential SCFA producer and it might play a role in reducing non-alcoholic steatohepatitis and/or liver fibrosis (53,54). Indeed, we observed a reduced hepatosteatosis in the OBE-ISR group with lower GLUT2, FAS, and SRBP1 (19). In addition, gut microbiota from the OBE-ISR group showed increased relative abundances of the genera Bifidobacterium, Bacteroides, Butyricimonas, Lachnoclostridium, Flavonifractor, Ruminiclostridium 5, and Faecalibaculum, indicating an improvement of these genera.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…At the genus level, treatment of ISR after 4 weeks revealed a higher proportion of Alistipes compared to the NOB group, which might be a bacterial genus of particular interest in the field of obesity since Alistipes is a potential SCFA producer and it might play a role in reducing non-alcoholic steatohepatitis and/or liver fibrosis (53,54). Indeed, we observed a reduced hepatosteatosis in the OBE-ISR group with lower GLUT2, FAS, and SRBP1 (19). In addition, gut microbiota from the OBE-ISR group showed increased relative abundances of the genera Bifidobacterium, Bacteroides, Butyricimonas, Lachnoclostridium, Flavonifractor, Ruminiclostridium 5, and Faecalibaculum, indicating an improvement of these genera.…”
Section: Discussionmentioning
confidence: 65%
“…Nonetheless, the quality of CHO is crucial for optimal glycemic control, insulin response, and weight management (13,41,42). In that context, we have previously reported that the OBE-ISR group improves insulin sensitivity and reduces dyslipidemia in growing rats, as well as GLP-1 augmented levels (19). Using a well-established HFD rodent model of childhood diet-induced obesity, we evaluated the effects of a specialized CHO diet on the gut microbiota composition by comparing its quality rather than its quantity (rapid digestible vs. slowly digestible CHO).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations